Systems Thinking: An introduction for Oxfam programme staff - and Bowman, Kimberly; Chettleborough, John; Jeans, Helen; Whitehead, James; Rowlands, Jo (Policy & Practice, 2015)
Development organizations frequently face and overcome challenges in programme delivery. But what happens when the proposed solutions fail? How can organizations adapt to changing conditions and ensure the benefits of programmes are shared as widely as possible?